Research progress of moyamoya disease combined with renovascular hypertension - Liu, Erheng; Zhao, Heng; Liu, Chengyuan; Tan, Xueyi; Luo, Chao; Yang, Shuaifeng (Frontiers in Surgery, 2022)
Moyamoya disease (MMD) is an idiopathic cerebrovascular disease which was first described by Suzuki and Takaku in 1969. Moyamoya disease is a non-atherosclerotic cerebrovascular structural disorder. MMD has been found all over the world, especially in Japan, Korea, and China. In recent years, many reports pointed out that the changes of vascular stenosis in patients with moyamoya disease occurred not only in intracranial vessels, but also in extracranial vessels, especially the changes of renal artery. Renovascular hypertension (RVH) is considered to be one of the important causes of hypertension in patients with moyamoya disease. The pathogenesis of moyamoya disease combined with renovascular hypertension is still unclear, and the selection of treatment has not yet reached a consensus. This article reviews the latest research progress in epidemiology, RNF213 gene, pathomorphology, clinical characteristics and treatment of moyamoya disease combined with renovascular hypertension, in order to provide reference for clinical workers.